Etiology of Recurrent Abdominal Pain in Children - Joshi, Binita Gurubacharya (Journal of Nepal Paediatric Society, 2013)
Introduction: Recurrent abdominal pain (RAP) is one of the most common gastrointestinal complaints during childhood and most frequent presentation in paediatric clinics. RAP has been classified etiologically into two broad groups: organic and functional. Functional causes of RAP were reported to be present in 90% of cases in the past. Because of the new diagnostic tools and an improved knowledge, the prevalence of RAP has been now increasing. The current study was done to find out the etiology of RAP in Nepalese children. Materials and Methods: This was a prospective study conducted in Civil Services Hospital, Paediatric department from April 2010 to March 2011 in children aged between 4 and 15 years, attending the outpatient department. All the children with RAP, who fulfilled the Apley’s criteria were included in this study. Results: Out of 47 children with RAP, organic causes were found in 41 children while non-organic causes, in 6 children. Parasitic infestation was the commonest organic cause of RAP, followed by idiopathic chronic constipation. Other causes were culture proven urinary tract infection, antral gastritis and H. pylori infection. Conclusion: Organic disorder is still the commoner cause of RAP in our part of the world. The key step in the management of RAP is to first investigate for the organic cause based on the symptoms. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7413 J Nepal Paediatr Soc. 2013;33(1):31-33